PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI MELALUI MOTIVASI TERHADAP KINERJA PEGAWAI ADMINISTRATIF - Pramita, Dyah Retno Ayu; Djawoto, Djawoto; Soekotjo, Hendri (STIE Mahardhika, 2020)
The existence of human resources in an organization has an important role. The progress of an organization can be seen from the performance of its human resources. Good performance of its human resources can lead the organization to achieve the goals set. The purpose of this study was to determine and analyze the influence of the work environment and compensation through motivation on the performance of the employees of Lembaga Layanan Pendidikan Tinggi (LLDITKI) Wilayah VII Surabaya. This research uses quantitative research approach. Samples taken in this study amounted to 68 people including all administrative staff of LLDIKTI Wilayah VII Surabaya. The independent variables in this study are Work Environment (LK) and Compensation (KM). The dependent variable in this study is Employee Performance (KP) and the intervening variable is Motivation (MV). The result showed that Work Environment had a positive and significant effect on Motivation, Compensation had a positive and significant effect on Motivation, Work Environment had a positive and significant effect on Employee Performance, Compensation had a positive and significant effect on Employee Performance and Motivation had a positive and significant effect on Employee Performance. While the sobel test result indicate that Motivation can mediate Work Environment and Employee Performance and Motivation can mediate Compensation and Employee Performance.